Solar Wind and Magnetospheric Conditions for Satellite Anomalies Attributed to Shallow Internal Charging - J. V. Rodriguez; B. T. Kress; N. Y. Buzulukova; R. J. Redmon (Space Weather, 2025)
Abstract Satellite charging in Earth's magnetospheric plasma and radiation belts frequently causes operational anomalies. A recent study of a frequent Space Wire anomaly on GOES linked it to shallow internal charging by 100–300 keV electrons. Solar wind and magnetospheric conditions during a period spanning solar minimum (2017–2021) are analyzed to gain further insight into the anomalies. The anomalies are divided into two groups, with inter‐anomaly intervals shorter than 2 days (clustered) and longer (background). The clusters sometimes exhibit a clear 27‐day recurrence. The magnetic local time (MLT) distributions for background anomalies are statistically uniform, unlike those for clustered anomalies, which peak prior to local noon. The clustered anomaly distributions with respect to Kp are similar to those for surface charging, indicating enhanced plasma sheet access to geostationary orbit. The maximum 100–300 keV fluxes during injections are similar to published extreme fluxes. Through superposed epoch analysis and comparison with published lists of high‐speed streams, clustered anomalies are determined to occur during high‐speed streams with elevated solar wind speed, lower number density, and weakly negative interplanetary magnetic field Bz. The MLT and Kp dependencies of the clustered anomalies may indicate charge accumulating in a thin dielectric with a time constant less than 1 day. The background anomalies, occurring uniformly in local time and varying slowly between solar rotation periods, may indicate a distinct charging location with a time constant greater than a solar rotation.